An updated review deciphering the anticancer potential of pentacyclic triterpene lupeol and its nanoformulations - AlMousa, Lujain A.; Pandey, Pratibha; Lakhanpal, Sorabh; Kyada, Ashish Kumar; H, Malathi.; Nayak, Priya Priyadarshini; Hussain, Arif; Hasan, Tarique Noorul; Alagal, Reham I.; Khan, Fahad (Frontiers in Pharmacology, 2025)
Triterpenoids from plants are essential sources of nutraceuticals, which possess numerous positive effects on human health. Lupeol (a pentacyclic dietary triterpenoid) is commonly present in edible fruits, vegetables, and medicinal plants. Numerous investigations on the pharmacological properties of lupeol have been carried out in the past 10 years, and the results have shown that the compound has enormous pharmacological properties, including antioxidant, anti-inflammatory, and anticancer properties. Research has shown that lupeol affects the functioning of numerous molecules, including the cytokines IL-2, NFκB, IL4, IL5, cFLIP, ILβ, and Bcl-2. Our review discusses recent advancements in plant lupeol and its underlying mode of action in combating human carcinoma within the timeframe spanning from 2010 to 2024. Also, we have tried to incorporate recent studies reported till date of the finalization of this review. In order to give researchers the most recent information, highlight the limitations of pertinent research at this time, and highlight both the mechanisms of action of lupeol and recent advances in its formulations that should be strengthened in future studies.